Wireless Power for Mobile Battery Charger - M. Fitra; Elvy S (Institute of Advanced Engineering and Science, 2017)
This Wireless Mobile Battery Charger project is using technique of inductive coupling. The basic concept of his technique was applied in transformer construction. With this technique, the power from AC or DC can be transfer through the medium of magnetic field or air space. In this project, the method is divided into two major activities which is to purpose circuit construction and to fabricate the prototype. The result is to evaluate the distance of power that can be transferred using technique of inductive coupling.